2008
DOI: 10.1007/s10458-008-9058-5
|View full text |Cite
|
Sign up to set email alerts
|

Get in touch: cooperative decision making based on robot-to-robot collisions

Abstract: We demonstrate the ability of a swarm of autonomous micro-robots to perform collective decision making in a dynamic environment. This decision making is an emergent property of decentralized self-organization, which results from executing a very simple bio-inspired algorithm. This algorithm allows the robotic swarm to choose from several distinct light sources in the environment and to aggregate in the area with the highest illuminance. Interestingly, these decisions are formed by the collective, although no i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 36 publications
4
148
1
Order By: Relevance
“…This single observation provides a strong motivation to the roboticist to understand biological systems and to exploit the solutions to which they have converged [3,4] (including to understand how biological solutions relate to probabilistic solutions [5]). This motivation is inspiring entirely novel (or, 'unconventional') approaches to mechanics [6], locomotion [7], sensing [8] and decision-making [9], to give only a handful of recent examples. At the same time, 'embodied' (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This single observation provides a strong motivation to the roboticist to understand biological systems and to exploit the solutions to which they have converged [3,4] (including to understand how biological solutions relate to probabilistic solutions [5]). This motivation is inspiring entirely novel (or, 'unconventional') approaches to mechanics [6], locomotion [7], sensing [8] and decision-making [9], to give only a handful of recent examples. At the same time, 'embodied' (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We use BEECLUST method [18] as the aggregation scenario. In BEECLUST, robots move randomly in the environment.…”
Section: Aggregation Methodsmentioning
confidence: 99%
“…Results of the performed experiments showed that robots are able to aggregate on the optimal zone where the intensity of the light is the highest. Schmickl et al [18] proposed two types of experiments: (i) static experiments in which there is a single light source and (ii) dynamic experiments in which there are two light sources with different intensities. The intensities of the sources are changed during an experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the evaluated individual behaviors of honeybees, 6,18 those behaviors are fitted in the described criteria of swarm robotics. 3 Inefficiency of a single bee to detect the optimal zone, simple perception of homogeneous individual agents, and effects of the population size are clearly illustrated in honeybee aggregation.…”
Section: Honeybee Aggregation Behaviormentioning
confidence: 99%